[Hummingbird Nest] - (:unkn) unknown (Stephens Ltd., Trinidad, 2010)
From a unique photo of Humming Bird and nest, Trinidad.
Colour: Sepia (print); Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Hummingbirds--Trinidad and Tobago; Birds--Trinidad and Tobago; Animals—Habitations--Trinidad and Tobago; Nests--Trinidad and Tobago